2007
DOI: 10.1103/physrevlett.98.046403
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Monte Carlo Study of an Interaction-Driven Band-Insulator–to–Metal Transition

Abstract: We study the transitions from band insulator to metal to Mott insulator in the ionic Hubbard model on a two dimensional square lattice using determinant Quantum Monte Carlo. Evaluation of the temperature dependence of the conductivity demonstrates that the metallic region extends for a finite range of interaction values. The Mott phase at strong coupling is accompanied by antiferromagnetic (AF) order. Inclusion of these intersite correlations changes the phase diagram qualitatively compared to dynamical mean f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
118
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 107 publications
(127 citation statements)
references
References 32 publications
9
118
0
Order By: Relevance
“…Recently the evolution of a band insulator (BI) into a Mott insulator upon increasing the interaction strength has been studied in the context of the ionic Hubbard model, 5,6,7,8,9,10,11,12 a two-band Hubbard model with crystal-field splitting, 13 and a bilayer model with two identical Hubbard planes coupled by single-particle hopping. 14,15,16,17,18 Different scenarios have emerged with the possibility of an intervening phase and continuous or discontinuous transitions at critical interaction strengths.…”
Section: Introductionmentioning
confidence: 99%
“…Recently the evolution of a band insulator (BI) into a Mott insulator upon increasing the interaction strength has been studied in the context of the ionic Hubbard model, 5,6,7,8,9,10,11,12 a two-band Hubbard model with crystal-field splitting, 13 and a bilayer model with two identical Hubbard planes coupled by single-particle hopping. 14,15,16,17,18 Different scenarios have emerged with the possibility of an intervening phase and continuous or discontinuous transitions at critical interaction strengths.…”
Section: Introductionmentioning
confidence: 99%
“…This bears a strong resemblance to the dispersion relation of the 2D IHM whose superlattice potential ∆ j (−1) j n j similarly has the effect of opening a band gap at q = (π, π), altering the ∆ = 0 dispersion relation ǫ q to E q = ± ǫ 2 q + ∆ 2 . Real space Quantum Monte Carlo (QMC) [8] has supplemented DMFT studies of the IHM [6] by allowing for magnetic order and concluded that U could cause the appearance of a metallic phase. However, despite the similarity in E q between the IHM and Eq.…”
mentioning
confidence: 99%
“…Analytic and numeric studies on such Hamiltonians are quite numerous. 17,18,31,32,33,34,35,36,37,38,39,40,41,42 It is useful to review the strong coupling (t = 0) phase diagram, since when the hopping is nonzero the topology of the phase diagram is rather similar qualitatively and even quantitatively. In the absence of an interaction with the lattice, the SDW phase, which consists of a collection of singly occupied sites, has energy E t=0 SDW = N V , while the CDW phase has alternating empty and doubly occupied sites, and energy E t=0 CDW = N U/2.…”
Section: Model and Computational Methodsmentioning
confidence: 99%
“…In this "ionic Hubbard model" the frozen distortions have an alternating pattern down the chain, 16 and an additional issue is the possibility that the band insulator at U = 0 and half filling is first driven metallic before becoming a SDW Mott insulator. 17,18 If the coupling of the electrons to the lattice is in the form of dynamically varying phonon degrees of freedom, one has the HubbardHolstein or Su-Schrieffer-Heeger Hamiltonian.…”
mentioning
confidence: 99%